Effect of Wheat and Barley Viscosity on Broiler Performance in Hamadan Province - Saki, A.A.; Alipana, A. (International Journal of Poultry Science, 2004)
Nutrient digestion and absorption could be inhibited by viscosity particularly in cereal diets on broiler feeding. This viscosity may be influenced by environmental condition and various cultivars in cereal. Experiment was conducted by complete random design (CRD). Four hundred and eighty Arian broiler chickens were used in two treatments includes, wheat and barely with 6 replicates and 40 chickens in each. Starter feeding recommended by NRC 1994 was used during the starter period (21 days of age). Experimental diets were arranged from 3 to 6 weeks of age. Similar condition such as temperature, moister, lighting, ventilation and drinking water were optimized for chicken. Feed intake (FI), feed conversion ratio (FCR) were recorded every week. Three chickens in each replicate were slaughtered as a random for consideration of gastrointestinal development in the end of experiment . No significantly differences were observed in FI, body weight (BW) and FCR, (P > 0.05). Although body weight was higher by wheat treatment compared with barley at 42 days of age. Where no response was appeared in gastrointestinal tract (P>0.05) in this particular case. The result of this study have shown that barley viscosity was higher than wheat but this was not significant.